Effective school characteristics as antecedents of teacher empowerment - Dahiru, Abbas Sani; Basri, Ramli; Lope Pihie, Zaidatol Akmaliah (IDOSI Publications, 2017)
Previous studies on teacher empowerment argued for strong educational leadership as an antecedent of teacher empowerment in schools. Rarely do studies examine factors such as effective school characteristics as antecedents of teacher empowerment. This study examined the effect of effective school characteristics on teacher empowerment. The research adopted a survey design and a total sample of 358 secondary school teachers in Zamfara State, Nigeria were selected through simple random sampling techniques from a total population of 4996 as a sample for the study, using Cochran’s sample size determination formula. Data were collected through survey method and were analyzed using both descriptive and inferential (Pearson correlation and multiple regression) statistical analyses. The findings of the study indicated the existence of significant and strong relationship between effective school characteristics and teacher empowerment. Furthermore, positive home/school relationship appeared to be the best contributor to teacher empowerment. This implies that efforts should be made to strengthen the effective school characteristics to empower teachers for the overall attainment of effective school system.